ANALISIS URGENSI PENYATUAN UNIT PENGELOLAAN PEMBIAYAAN DAN UNIT PENGELOLAAN KAS - Hari Sugiyanto (SUBSTANSI, 2017)
As a country that is being actively carrying out development, Indonesia needs huge funds to fund it. The Government has conducted a wide range of strategic actions and efforts with a variety of policy instruments, one of which is the policy that is contained in the budget revenue and expenditure of the State (State Budget).State Budget as an instrument of Government policy as a form contains two major elements, namely income and spending. Over the years, the Government has embraced the familiar deficit in the budget, so that the financing needed to close the deficit. Management of revenue and expenditures needs the right policy because it involves a huge amount of cash. DJPBN has the task so that the existing cash or cash that is needed can be managed with proper, whereas DJPPR have a duty to let the deficit contained in the budget does not become a big problem.Based on the analysis of brief, DJPBN have difficulty in estimating the amount of cash that is right, the difficulty in determining when there is enough cash when paying bills on time, and investment cash towards the unemployed. Such difficulties should be aided by the existence of financing (debt) which its implementation be DJPPR task. But in fact the difficulties could not be overcome, because most of the policies that break, and or less coordination between the 2 units of Echelon I at the Ministry of Finance.